The Influence of Product Quality, Price Perception, and Brand Ambassadors on Product Purchase Decisions Garnier Facial Cleansing Soap - Syifa Mutiara Rachmah; Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine how much influence the influence of product quality, price perception, and brand ambassadors has on purchasing decisions for Garnier facial cleansing soap products in Jakarta. Data for primary data was used in this study to 100 respondents in the Garnier product respondent questionnaire. The analysis used in this study is SPSS version 23 which is used in the analysis of this study is multiple linear regression. The finding demonstrated that Product Quality, Perceived Price, and Brand Ambassador have a positive and significant impact on decisions to purchase Garnier products. This indicates that Garnier will increase purchasing decisions if it influences Product Quality, Perceived Price, and Brand Ambassador. The coefficient of determination (Adjusted R Square) value of 0.616 indicates that the factors Product Quality, Perceived Price, and Brand Ambassador perception contribute 61.6 %to the decision to purchase Garnier products, while other factors that were not examined influence 38.4%.